Why the “journey” of carbon neutrality is a long one—a mixed method research based on carbon emission trading in hubei province - Jiang, Yihan; Yao, Jiayi; Gao, Ruosu; Chen, Jiaying (Frontiers in Environmental Science, 2022)
This paper aims to explore the effectiveness of carbon emissions trading system by using hybrid research. In the past five years, the development level of carbon finance in Hubei Province is in the first tier. Hubei carbon emission trading center was established in September 2012, and now ranks top in the trading volume and total transaction amount of China's seven pilot exchanges. Therefore, choosing Hubei Province as a sample to study the carbon emissions trading system has good externalities, that is, the research conclusions are highly representative. In order to make an in-depth analysis of the system construction and operation effect of the environmental equity trading market of carbon emission rights, this paper uses the closure of Hubei Province as an instrumental variable to alleviate the endogeneity in previous studies, and makes an empirical study on the effectiveness of the carbon emission trading system. The study finds that: after alleviating endogeneity, the current carbon emissions trading has reduced air quality. At the same time, this paper theoretically and statistically verifies the correlation and exogenous of the instrumental variable of city closure to ensure the credibility of the results. This paper further analyzes and finds that the lower the degree of industrialization and the worse the air quality, the higher the degree of air quality reduction. In addition, this paper conducted a series of robustness tests, such as adding new traffic related control variable, replacing variable indicators of air quality, conducting placebo test, and conducting lag regression, which verifies that the benchmark regression results are still valid. In the mechanism part, this paper uses the methods of interview and case analysis to analyze the causal mechanism of this phenomenon from the perspective of the system itself and the challenges in the implementation process. As far as the system itself is concerned, this paper believes that the current carbon emissions trading system does not cover a comprehensive range, there are defects in the way of carbon quota allocation, and the accuracy of the current verification method needs to be tested; In the process of implementation, there are "local protectionism" and information asymmetry.